2018
DOI: 10.1093/jbcr/iry029
|View full text |Cite
|
Sign up to set email alerts
|

A Comparative Study of the ReCell® Device and Autologous Split-Thickness Meshed Skin Graft in the Treatment of Acute Burn Injuries

Abstract: Early excision and autografting are standard care for deeper burns. However, donor sites are a source of significant morbidity. To address this, the ReCell® Autologous Cell Harvesting Device (ReCell) was designed for use at the point-of-care to prepare a noncultured, autologous skin cell suspension (ASCS) capable of epidermal regeneration using minimal donor skin. A prospective study was conducted to evaluate the clinical performance of ReCell vs meshed split-thickness skin grafts (STSG, Control) for the treat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
62
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 74 publications
(62 citation statements)
references
References 19 publications
0
62
0
Order By: Relevance
“…The presence of melanocytes in the cell suspension also had a favorable impact on final pigmentation compared with other systems. 78 When compared with meshed autograft, ReCell had a slightly more favorable final pigmentation, and was similar to unmeshed graft with respect to final pigmentation. 78 Disadvantages of the system include high cost and loss of cells during spraying.…”
Section: Recellmentioning
confidence: 93%
See 2 more Smart Citations
“…The presence of melanocytes in the cell suspension also had a favorable impact on final pigmentation compared with other systems. 78 When compared with meshed autograft, ReCell had a slightly more favorable final pigmentation, and was similar to unmeshed graft with respect to final pigmentation. 78 Disadvantages of the system include high cost and loss of cells during spraying.…”
Section: Recellmentioning
confidence: 93%
“…78 When compared with meshed autograft, ReCell had a slightly more favorable final pigmentation, and was similar to unmeshed graft with respect to final pigmentation. 78 Disadvantages of the system include high cost and loss of cells during spraying. 65 StrataGraft StrataGraft (Stratatech-Mallinkcrodt, Madison, WI) is a stratified bilayer skin substitute that has shown great promise, earning an "orphan product" designation from the FDA in 2012 and "Regenerative Medicine Advanced Therapy" designation in 2017.…”
Section: Recellmentioning
confidence: 93%
See 1 more Smart Citation
“…The cell suspension predominantly contains keratinocytes (>64%), but also includes significant populations of fibroblasts and viable melanocytes . Holmes et al completed a comparative clinical study of RECELL and autologous split‐thickness skin grafting in the treatment of acute burns, where the clinical outcomes of the former were as effective as the latter while requiring almost 40 times less donor tissue . Patients in this study reported significantly less pain at the donor sites, perceived greater improvement in wound appearance, and expressed overall higher satisfaction than patients receiving skin grafts.…”
Section: Advanced Tissue Engineering Approaches To Regenerate Skinmentioning
confidence: 99%
“…The most recently approved burn treatment, RECELL, received approval in September 2018. It began clinical trials in 2010 and has since been used on approximately 250 patients in the US, either as part of the clinical trial protocol or under compassionate use . Clinical trials for regenerative medicine therapies often require a long‐time enroll enough subjects to meet the study requirements or long‐term endpoints to ensure safety.…”
Section: Current Perspectives and Future Directions Of Skin Tissue Enmentioning
confidence: 99%